Elaboración de un plan estratégico para la cooperativa de ahorro y crédito y vivienda Casa Fácil de la ciudad de Loja, provincia de Loja - Bahamonde Sánchez, Roberto Carlos (2015)
Strategic planning today is considered one of the most important tools for organizations to proyectase in time and achieve compliance with its long-term goals by leveraging their ability to influence the environment and to create opportunities to assimilate the environment for their benefit. The aim of this study is to develop a Strategic Plan for Cooperative Savings and Easy House Loja province of Loja, which encourages all members of the organization to bringing success to the cooperative, be competitive, innovative using new strategies to reach a position in the market. In addition to strategic planning it is intended to somehow adopt viable alternative solutions to the many shortcomings of the institution, minimizing the threats, strengthening weaknesses and potentiate both the strengths and opportunities, enabling the effective and efficient achievement of its goals and objectives institutional, focused on strengthening different areas of the cooperative, thus improving the image and progress of the cooperative Easy House; with the aim to strengthen the administrative and financial management. So the manager of the cooperative must first be aware of and in contact with the internal and external environment so you can identify the problems that arise daily, especially beware of personnel management and applying the following methods: Scientific; Descriptive; Mathematician - Analytical; Inductive and deductive, and the following techniques: Direct Observation; Interview and Survey. That is why the credit union "Easy House Ltda." Loja city, a strategic plan in which options that help contribute in some way to the improvement and development of administrative activities have been developed and This financial entity. This plan aims to reform the administrative and financial management of the cooperative, to do some methods which are then detailed what was used, the scientific method that allowed the theoretical and conceptual foundation for the basics of management, financial companies, Philosophy business, strategic planning, SWOT, EFE Matrix and EFI, weighting, among others, the same who helped direct the development of the thesis, the inductive and deductive method allowed to deduct the conclusions and recommendations for the cooperative. In addition, technical jobs, including direct observation, interview the manager and 6 employees of the financial institution and surveys of 357 partners who helped to determine the internal and external problems of the credit union "Casa Easy Ltda. "Loja city, they have not been allowed to develop in a better way. After this exposure and discussion of results which was the starting point for the proposal comprising 4 strategic objectives that gives an alternative to improve the proper functioning of the cooperative and thus attract more partners and resources we are made financial. Through the proposed Strategic Plan it is intended that the institution has a clear view of the situation in which it is to provide the service and make a proposal to allow the institution to develop its activities efficiently and competitive with other institutions of the same nature, also enabling a greater degree of satisfaction of the partners. According to the diagnosis made by the financial institution, the following proposals thereof containing the following strategic objectives to counter threats to the environment is made: 1. Conduct an organizational structure to be efficient organization and financial administration. 2. Develop a manual of administrative and financial procedures for the proper functioning of the cooperative financial processes and staff. 3. Train staff in order to make their activities more efficient and eliminate existing operational problems. 4. Perform aggressive advertising campaigns to publicize the services and the existence of cooperative agreements made with the advertising media with low costs to achieve welcome more partners. 9 These strategic objectives are proposed with the aim of increasing innovation, productivity, performance and positive employee attitude and a social responsibility of those who make the Cooperative "Easy House Ltda." I have finally been able to reach conclusion and recommend the most feasible for this financial institution to increase its market coverage and thus provide an effective service to the community. The literature has been used to develop the conceptual framework, the annexes are the means by which the information needed for the development of this work was obtained. The budget for this strategic plan comprises an amount equivalent to $ 8,770, a value that current plans to invest in shares, considered a coordinated action guide and a key to control the productivity of the cooperative basic